Non-University Higher Education in Europe
XVI, 262 p.
Keywords: This book represents the first-of-its-kind comprehensive discussion of the non-university higher education sector in Europe. Higher education throughout the world is facing rapid change. Despite the enormous attention devoted to that reality, this volume fills an important void. It describes and offers critical comparisons between the systems in 10 European countries. The book brings together the thinking of leading scholars on the non-university sectors in Austria, Belgium, Finland, Germany, Ireland, the Netherlands, Norway, Portugal, Spain, and the United Kingdom, with a chapter devoted to each country. National case studies are presented for the non-university sector in these countries that address issues such as historical developments, policy changes, governance structures, levels of institutional autonomy and future trends. The editors offer a critical comparative analysis of the systems in these countries followed by a probing look into the future of the non-university sector in Europe. The book is essential reading for those who want a comprehensive, timely and in-depth understanding of the European non-university sector. It will be informative to anyone involved in system or institutional governance, as well as those pursuing research. It should be a reference in every institutional library.